RURAL DEVELOPMENT APPROACH IN ITALY: EXAMPLE ON AREA OF TEVERINA AS A POSSIBILITY FOR DANUBE REGION- ОРИГИНАЛНИ НАУЧНИ РАД - Panin, Biljana; Cortignani, Raffaele (Economics of Agriculture, 2011)
In recent years territorial cohesion has become an important issue for national and supranational governments. This concern came from the growth in differences and imbalance in terms of economic development. Urban and more developed areas are attracting more people and economic activities, while a great part of rural and peripheral territories have the trend of abandonment and underdevelopment. This paper shows on example of the territory of Teverina in Italy how bottom-up policies can be used and territorial marketing approach in order to achieve sustainability of the area, attract investments and to support the goal of community. Based on area of Teverina example, paper gives recommendations that can be useful for regional development of Danube region.